Resistência natural da madeira de três espécies da caatinga a um fungo de podridão parda - Santos, Marina Beatriz da Silva Bezerra (Universidade Federal Rural do Semi-Árido, 2018)
Studding woods and their aspects is very important. Just as, knowing the resistance of species to deterioration is a tool to optimize their uses and production to the market. On that basis, the aim of this work was evaluate the natural resistance of three typical Caatinga's species, Jurema-Preta (Mimosa tenuiflora (Mart.) Benth.), Sabiá (Mimosa caesalpiniaefolia Benth) and Pereiro (Aspidosperma pyrifolium Mart.), to the attack of a fungus species (Daldinia sp.) that causes brown rot in laboratory's decay test. All species showed high resistance to the studied fungus. Solubility analyzes in 1% NaOH showed that all species showed deterioration of cellulose, where Jurema-Preta and Pinus did not obtain statistical differences after the test, however, Sabiá and Pereiro presented higher solubility levels indicating a higher degradation of cellulose by the fungus in these species. With colorimetry, it was possible to observe that all species got darker after the attack presenting a pattern of color variation after the deterioration. The Pereiro was the species that showed higher color variation, followed by Pinus and Jurema-Preta, which didn't showed difference between them. The Sabiá was the one which obteined lower color variation. The Pereiro also showed color variation between two groups of samples, that indicated different deterioration levels. This result showed that the natural resistance can varies within a species.
Monografia
Keywords: Teste de apodrecimento em laboratório; Daldinia sp.; Colorimetria; Laboratory's decay test; Daldinia sp.; Colorimetry; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL